Effect of globin peptide on female fertility in aging granulosa cell-specific Nrg1 knockout mice - Takashi UMEHARA; Marino OGASAHARA; D.M.V. Supun PREMARATHNE; Yuka SASAKAWA; Yasuo SUMIDA; Masayuki SHIMADA (The Society for Reproduction and Development, 2024)
Ovarian fibrosis contributes to age-related ovarian dysfunction. In our previous study, we observed ovarian fibrosis in both obese and aging mice with intracellular lipid droplets in the fibrotic ovaries. Although the importance of mitochondria in ovarian fibrosis has been recognized in pharmacological studies, their role in lipid metabolism remains unclear. Globin peptide (GP), derived from hemoglobin, enhances lipid metabolism in obese mice. This study aimed to elucidate the importance of lipid metabolism in ovarian fibrosis by using GP. Treatment of ovarian stromal cells with GP increased mitochondrial oxygen consumption during β-oxidation. Lipid accumulation was also observed in the ovaries of granulosa cell-specific Nrg1 knockout mice (gcNrg1KO), and the administration of GP to gcNrg1KO mice for two months reduced ovarian lipid accumulation and fibrosis in addition to restoring the estrous cycle. GP holds promise for mitigating lipid-related ovarian issues and provides a novel approach to safeguarding ovarian health by regulating fibrosis via lipid pathways.